Tax Administration of Large Taxpayers in Some CEE and CIS Countries - Bogovac, Jasna; Soloveva, Natalia; Radvan, Michal; Marczak, Jarosław; Uvarova-Patenko, Natalia (Public Governance, Administration and Finances Law Review, 2018)
We compare tax administration of large taxpayers in Croatia, the Czech Republic, Russia, Poland and Kazakhstan. Our hypothesis is that these units of tax administrations play an important role in collecting public revenue as well as preventing tax evasion in a dynamic global economy. We provide evidences about the most important characteristics of large taxpayer offices, their normative definitions, scope of work and positive as well as negative aspects of their practice. Some data are compared between countries and some for each country separately, due to the fact that differences in the above-mentioned countries, in size, economic and political aspects, vary substantially. Moreover, we were confronted with the limited scope of available information what made our comparison even more challengeable. Therefore, this work is, in a way, a “pioneer” attempt to compare specific national LTOs in one place. Our findings support the discussion that prove the hypothesis and enable recommendations.